MAKNA KEWIRAUSAHAAN PADA ETNIS JAWA, MINANG, DAN TIONGHOA: SEBUAH STUDI REPRESENTASI SOSIAL - Sutanto, Okki; Nurrachman, Nani (Konsorsium Psikologi Ilmiah Nusantara (KPIN), 2018)
Abstract — The important link between culture and entrepreneurship has often been overlooked by psychological research on entrepreneurship. The present study explores the meaning of entrepreneurship among three ethnic groups in Indonesia: Javanese, Minangese, and Chinese. Using the perspective of social representation theory, especially the structural approach, this study employs the mixed-method design. By using quantitative approach with Hierarchized Evocation method on 122 subjects the attributes and structure of entrepreneurship’s social representation were discovered. The central core elements of the Javanese were autonomy and hard work, the Minangese were trading, products, capital, and autonomy, and for the Chinese were strategy and management and hard work. The qualitative approach using interview conducted on 11 entrepreneurs found that each ethnic group views entrepreneurship differently. The different views manifested on several aspects such as the motivation to start a business, the important values and views regarding entrepreneurship. Some attributes which were found to be unique for each ethnic were honesty and nrimo for the Javanese, observance to religion and belongingness to one’s hometown for the Minangese, and creativity and patience for the Chinese.Abstrak — Pentingnya kaitan budaya dalam kewirausahaan belum banyak digali oleh penelitian Psikologi di bidang kewirausahaan. Studi ini mengeksplorasi pemaknaan kewirausahaan pada tiga etnis di Indonesia yakni Jawa, Minang, dan Tionghoa, dengan menggunakan perspektif representasi sosial, khususnya pendekatan struktural. Desain penelitian mixed-method digunakan dalam studi ini. Pada pendekatan kuantitatif dengan teknik Hierarchized Ecovation pada 122 responden berhasil memetakan atribut dan struktur representasi sosial tentang kewirausahaan. Pendekatan kualitatif melalui wawancara pada 11 responden menemukan perbedaan pemaknaan kewirausahaan termanifestasi dalam tiga hal yakni alasan berwirausaha, nilai dan hal yang dianggap penting dalam berwirausaha, dan proses pelestarian nilai-nilai kewirausahaan. Ditemukan bahwa central core pada etnis Jawa adalah kemandirian dan kerja keras, sedang pada etnis Minang adalah berdagang, produk, modal, dan kemandirian, dan pada etnis Tionghoa adalah strategi dan manajemen serta kerja keras. Sejumlah atribut yang menjadi kekhasan masing-masing etnis yakni kejujuran dan nrimo pada etnis Jawa, kesalehan pada agama dan kecintaan pada kampung halaman pada etnis Minang, serta kreativitas dan kesabaran pada etnis Tionghoa.